Miconazole in systemic candidosis. - Hatala, M (1977)
Results are reported on the effect of miconazole together with concurrent medication in the treatment of 7 patients with systemic candidiasis. Two patients were discharged from hospital in good condition. In two others, the clinical status normalized. One patient's status improved but he was subsequently readmitted. Two patients died. The excellent tolerance of miconazole by all patients was a particular feature of this trial.